Pengaruh Model Pembelajaran Kontekstual Berbantuan Media LKS terhadap Pemahaman Konsep Sains Siswa - Nurhamida, Ida; Utami, Septiana Dwi; Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The purpose of this study was to determine the effect of the contextual learning model assisted by LKS media on the understanding of science concepts in eighth grade students of SMP Negeri 1 Lape, Sumbawa Regency. The type of research used in this research is Quasi Experiment (quasi-experimental). The research design used in this study was a pre-test post-test control group design. The population in this study were all eighth grade students of SMP Negeri 1 Lape, Sumbawa Regency for the 2020/2021 academic year. The sample in this study were 2 classes, each of which became the experimental class and the control class. Sampling was done by purposive sampling technique. The instruments in this study were the Learning Implementation Plan (RPP), Student Worksheets (LKS), and concept understanding tests. The data analysis technique used t-test at a significance level of 5%. The results obtained that the average pre-test value in the experimental class was 57 and in the control class was 58.25. The results of the pre-test and post-test in the experimental class are 45 and 70, while in the control class are 40 and 75. The results of the t-test are obtained tcount = 1.816 and ttable = 1.689, then H0 is rejected and Ha is accepted, so there is a significant difference between students' understanding of science concepts in the experimental class and students' understanding of science concepts in the control class. So it can be concluded that there is an influence of the contextual learning model assisted by LKS media on the understanding of science concepts for eighth grade students of SMP Negeri 1 Lape, Sumbawa Regency.